Seeking the Ideal Level of Design Newness: Consumer Response to Radical and Incremental Product Design1. (1st September 2013) - Mugge, Ruth; Dahl, Darren W.
Abstract : To develop successful new products, new product development managers need to have a thorough understanding of the consumer adoption process, specifically in how consumers evaluate new products. This research examines the value of product design for consumers' evaluation of radical and incremental innovations. The primary goal was to empirically test how design newness affects consumer response to product innovations. Design newness (also referred to as novelty or atypicality) is defined as the deviation in a product design from the current design state of a certain product category. Although prior research has suggested that higher levels of design newness may have a positive effect on consumers' evaluations of new products, higher levels of design newness may also have negative consequences for consumer response to radical innovations. An experimental context ( n  = 130) using systematically designed products for three product categories was used to test how consumers respond to high and low levels of design newness for both radical and incremental innovations. The findings show that for radical innovations, embodying the product in a design with a low (versus high) level of design newness led to more positive evaluations and less learning‐cost inferences. Because the functional attributes of a radical innovation are incongruent to existing products, consumers find it difficult to access the relevant product category schema in order to transfer knowledge to the new product. Because of this poor knowledge transfer, consumers may feel that they lack the ability to make effective use of the radical innovation, resulting in greater learning costs. In this case, a product design with a low level of design newness can provide consumers with a frame of reference for understanding the radical innovation. Contrasting this result, no difference was found between a low and a high level of design newness for incremental innovations. For incremental innovations, by definition the functional attributes characteristic to the innovation are highly comparable with those products that are already stored in consumers' memory. Thus, there is no need for an additional reconfirmation of the preexisting schema through product design, and consumers are able to access the relevant schema regardless of the level of design newness inherent in the product. These findings are integrated into a discussion of the managerial implications and the potential avenues for future research.